Experimental Analysis of the Use of Lecture and Role-Play Methods in Islamic Religious Education Learning - Ikhwana Ikhwana (Integrasi: Jurnal Studi Islam dan Humaniora, 2026)
This study aims to experimentally analyze the differences in students’ learning outcomes in Islamic Religious Education (IRE) taught using the lecture method and the role-play method. The research employed a quantitative approach with a quasi-experimental design involving two groups: an experimental group and a control group. The experimental group was taught using the role-play method, while the control group was taught using the lecture method. Data were collected through learning achievement tests administered before (pre-test) and after (post-test) the treatment. Data analysis was conducted using a t-test to determine differences in learning outcomes between the two groups. The results indicate a significant difference in learning outcomes between students taught using the role-play method and those taught using the lecture method. Students who participated in role-play-based learning demonstrated higher improvement in learning outcomes compared to those taught using the lecture method. Therefore, the role-play method is considered more effective in enhancing learning outcomes in Islamic Religious Education.